Manual of research techniques in cardiovascular medicine - Ardehali, Hossein; Bolli, Roberto; Losordo, Douglas (Wiley, 2014)
While some research methods or techniques are applicable in several areas of medicine, research in cardiovascular diseases requires knowledge of an increasing array of procedures, techniques and measurements that are highly specialized and unique to this area of investigation. Edited by senior clinical investigators who are recognized leaders in cardiovascular medicine worldwide, this book provides readers with a comprehensive, practical "how-to-do-it" review of best-practice techniques for cardiovascular research